Politik Identitas Pada Pemilihan Gubernur Sumatera Utara tahun 2018 - Dauly, Sayed Muhammad; Kusmanto, Heri; Kadir, Abdul (Universitas Medan Area, 2019)
This study explains the process of identity politics that occurred in the gubernatorial election in North Sumatra in 2018. The purpose of this study is to look at the process of identity politics and patterns of identity politics influencing the course of democratic parties between contesting candidate pairs. This study uses a descriptive method that focuses on the actual problems or phenomena that occur when the research is conducted. The findings of this study are: (1) The identity politics process was carried out by the ERAMAS team by evaluating traditional and religious leaders, while the DJOSS team only carried out the process of identity politics by using traditional leaders in various regions; (2) The patterns of identity politics in the ERAMAS team are carried out in the form of activities related to Islam, such as preaching safari with Ustadz Abdussomad, Dzikir Akbar, provider of mosque cleaning cars, subuh movement in congregation, and sanitation, and participating in traditional activities DJOSS's winning team patterned activities related to adat in various regions and were involved in traditional activities, for religious patterns only to visit religious leaders in the area.